PERCEPTIONS OF ATHLETES AT THE EAST JAVA PETANQUE PROVINCIAL TRAINING CENTER REGARDING PHYSICAL TRAINING - Kuncoro Adi Sugiarto; Nurkholis; Rini Ismalasari; Billy Emir Rizkanto (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Physical training is a fundamental component in athlete development for petanque, as it determines the arm strength, balance, concentration, and endurance required for shooting and pointing techniques. This study aims to describe the perception of athletes at the Regional Education and Training Center (Puslatda) for Petanque of East Java toward the physical training program they undergo. The study employed a quantitative descriptive approach using a survey technique with a Likert-scale questionnaire. The population consisted of all Puslatda Petanque East Java athletes, with a total sampling technique involving 20 athletes. Data were analyzed using descriptive percentage-based statistics and categorized into five levels of perception. The results indicate that athletes' overall perception of physical training falls into the very positive category, with a mean score of 82.0%. The training method and variation indicator obtained the highest percentage (84.1%), while the coach's role indicator obtained the lowest percentage (80.3%), although both remained within the positive to very positive range. These findings suggest that Puslatda Petanque East Java athletes generally perceive their physical training program positively, and are expected to serve as evaluation material for coaches and petanque sport administrators in East Java, particularly in strengthening coach-athlete communication and feedback.